2012
DOI: 10.1128/mmbr.00023-12
|View full text |Cite
|
Sign up to set email alerts
|

Enterococci in the Environment

Abstract: SUMMARYEnterococci are common, commensal members of gut communities in mammals and birds, yet they are also opportunistic pathogens that cause millions of human and animal infections annually. Because they are shed in human and animal feces, are readily culturable, and predict human health risks from exposure to polluted recreational waters, they are used as surrogates for waterborne pathogens and as fecal indicator bacteria (FIB) in research and in water quality testing throughout the world. Evidence from sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
418
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 564 publications
(445 citation statements)
references
References 346 publications
17
418
0
10
Order By: Relevance
“…Additionally, ermB was only detected in one interband sample in the first year of the crop rotation, while Garder et al (2014) detected ermB and ermF at quantifiable levels in every interband sample in the two previous years (fall 2010-spring 2012). The drought conditions in the summer of 2012 in Northeast Iowa may have caused additional stress to bacteria hosting the resistance genes and therefore hastened the return of overall concentrations to those found in no-manure control plot soils (Cools et al, 2001;Byappanahalli et al, 2012). The reduction in ermB and ermF genes in soil over winter are similar to those reported previously (Garder et al, 2014;Fahrenfeld et al, 2014).…”
Section: Discussionsupporting
confidence: 75%
“…Additionally, ermB was only detected in one interband sample in the first year of the crop rotation, while Garder et al (2014) detected ermB and ermF at quantifiable levels in every interband sample in the two previous years (fall 2010-spring 2012). The drought conditions in the summer of 2012 in Northeast Iowa may have caused additional stress to bacteria hosting the resistance genes and therefore hastened the return of overall concentrations to those found in no-manure control plot soils (Cools et al, 2001;Byappanahalli et al, 2012). The reduction in ermB and ermF genes in soil over winter are similar to those reported previously (Garder et al, 2014;Fahrenfeld et al, 2014).…”
Section: Discussionsupporting
confidence: 75%
“…In 1984, enterococci were given formal genus status, after genetic (DNA-DNA and DNA-RNA hybridization) studies demonstrated a more distant relationship with the streptococci. The Enterococcus was proposed as a unique genus, separate from Streptococcus (Byappanahalli et al 2012). According to ISO 7899-2, intestinal enterococci are able to reduce 2,3,5-triphenyltetrazolium chloride to formazan and to hydrolyse esculin at 44°C on the selective media, Slanetz and Bartley agar, containing sodium azide, which inhibits the growth of Gram-negative and staphylococci.…”
Section: Conventional Indicators Of Fecal Contaminationmentioning
confidence: 99%
“…Enterococcus species are Gram-positive bacteria belonging to the gastrointestinal microbiota of humans and animals, mammals and birds, and are widely distributed in the environment such as terrestrial and water habitats [1]. Some 42 ± 1°C for 18-24 h. From plates with growth of colonies typical for enterococci, at least one colony was subcultured on KAAA.…”
Section: Introductionmentioning
confidence: 99%